2014
DOI: 10.1007/s00330-014-3459-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of image quality and low-contrast detectability in abdominal CT of obese patients: comparison of a novel integrated circuit with a conventional discrete circuit detector at different tube voltages

Abstract: The IC detector at 100 kVp resulted in similar low-contrast detectability compared to the conventional detector with a 120-kVp protocol at a radiation dose reduction of 37 %.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…This results in a higher image quality and a reduction of radiation dose for low tube current protocols because less photons are traversing the patient. 3,15 In our study, image noise was significantly reduced up to 71.6% in images obtained with 1/8 of the standard dose using ADMIRE 5 compared with FBP and led to an improvement of the subjective image quality.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…This results in a higher image quality and a reduction of radiation dose for low tube current protocols because less photons are traversing the patient. 3,15 In our study, image noise was significantly reduced up to 71.6% in images obtained with 1/8 of the standard dose using ADMIRE 5 compared with FBP and led to an improvement of the subjective image quality.…”
Section: Discussionsupporting
confidence: 50%
“…Subsequently, statistical optimization of the data is performed, reaching a target noise reduction which depends on the selected ADMIRE strength level. 15,16 Compared with the antecessor SAFIRE (sinogram affirmed iterative reconstruction), ADMIRE offers a higher resolution at organ borders, improving delineation of edges and thus is beneficial also for pulmonary nodule detection. 15 Subsequent analyses were performed using a picture archiving and communication system (Impax, V. 6.5.5.1033; Agfa-Gevaert, Mortsel, Belgium) on a high-definition liquid crystal display monitor (Barco™; Medical Imaging Systems, Kortrijk, Belgium).…”
Section: Data Reconstructionmentioning
confidence: 99%
“…Although technical improvements like integrated circuit detectors and iterative reconstructions have led to an improved image quality in CT while radiation dose could be markedly reduced, artifacts due to implanted metal-containing materials such as endoprostheses and coils are an enduring challenge in CT examinations and can hamper clinical diagnosis (1)(2)(3). Besides image interpretation, artifacts from high-density objects represent a severe problem for radiation therapy planning and attenuation correction in positron emission tomography CT (PET-CT) (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…The purified energy spectrum improves material resolution, and a larger pitch (2.0) can be selected, which is more effective in reducing radiation dose. Euler et al [17] used a Stellar photon detector with reduced electronic noise and an iterative reconstruction algorithm and found that this method not only reduced the radiation dose for chest examination by 45.6% but it also improved the signal-to-noise ratio and contrast noise ratio of the image. In this study, image noise and the contrast nose ratio from the Sn100-LDCT scan were significantly higher than from the ECG-CT scan, but the calcified branches of the coronary arteries in the ECG-CT scan were all shown in the Sn100-LDCT scan, and the coronary artery calcification score was calculated without omission.…”
Section: Discussionmentioning
confidence: 99%